2002
DOI: 10.2223/jped.902
|View full text |Cite
|
Sign up to set email alerts
|

Tympanostomy tubes and water

Abstract: Objective: an in vitro study was conducted to set the necessary pressure in fluids that could break resistance and cross the opening of a tympanostomy tube.Methods: a water column model was created and graduated in centimeters from base to top. We adapted three sorts of ventilation tubes. In each model, fluids were tested (tap water, seawater, river water, soapy water and eardrops). The column was filled with fluid until a threshold was reached, flowing through the tube opening. The threshold was registered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…( 3 - 6 ) Some experimental studies have also shown that the water traverses the ventilation tube only under pressure, or when it is mixed with substances that decrease its surface tension, such as soap. ( 7 , 8 ) Thus, the precautions given would be unnecessary, decreasing the inconvenience and the deprivations caused in the everyday life of operated children.…”
Section: Introductionmentioning
confidence: 99%
“…( 3 - 6 ) Some experimental studies have also shown that the water traverses the ventilation tube only under pressure, or when it is mixed with substances that decrease its surface tension, such as soap. ( 7 , 8 ) Thus, the precautions given would be unnecessary, decreasing the inconvenience and the deprivations caused in the everyday life of operated children.…”
Section: Introductionmentioning
confidence: 99%